Treatment of Advanced Metastatic Melanoma - Pietro Quaglino; Paolo Fava; Luca Tonella; Marco Rubatto; Simone Ribero; Maria Teresa Ferro (Mattioli1885, 2021)
The introduction in clinical practice of new drug compounds both targeted therapies anti-BRAF and checkpoint inhibitors have largely improved our potential to manage advanced metastatic melanoma patients. This has led to a significant improvement in terms of response rates and particularly in the overall survival (OS). The long-term results of trials with follow-up data of patients treated with targeted or immunotherapies reported median OS rates around 24 months, with 5-year survival rates around 35-40%. As to the drugs currently available and reimbursed by the Italian National Health System, 3 combinations of anti-BRAF/anti-MEK inhibitors are available (dabrafenib/trametinib, vemurafenib/cobimetinib and the most recently introduced encorafenib/binimetinib). As for checkpoint inhibitors, first line immunotherapy is represented by anti-PD1 blockers (nivolumab and pembrolizumab), whilst the anti-CTLA-4 ipilimumab can be used as second line immunotherapy. The decision-making factors that define the best treatment approach in stage IV patients with metastatic melanoma include the mutation pattern, performance status, high/low tumor load, brain metastases, progression pattern (low/fast), and availability of clinical trials. This review will analyze the current therapeutic tools adopted for the treatment of metastatic melanoma patients. It will then focus on the latest results obtained by novel treatments (checkpoint inhibitors and targeted therapies) which can be used in the clinical daily practice.